Land of wolves eaudiobook - Johnson, Craig (Walt Longmire Mystery, 2019)
The new novel in Craig Johnson's beloved New York Times bestselling Longmire series. Attempting to recover from his harrowing experiences in Mexico, in Land of Wolves Wyoming Sheriff Walt Longmire is neck deep in the investigation of what could or could not be the suicidal hanging of a shepherd. With unsettling connections to a Basque family with a reputation for removing the legs of Absaroka County sheriffs, matters become even more complicated with the appearance of an oversize wolf in the Big Horn Mountains to which Walt finds himself feeling more and more empathetic.